Examining Power System Resilience From the Perspective of Consumers: A Review - Saranga K. Abeygunawardane; Visvakumar Aravinthan; Xiaoheng Wang; Anil Pahwa; Chanan Singh (IEEE Access)
This paper presents a comprehensive review of power system resilience through the lens of power consumers. As consumers play a pivotal role within the power system by being end users and ultimate cost-bearers, understanding how consumers perceive and experience resilience is crucial. We examine the factors influencing consumer perspectives on power system resilience, including quality of service, energy burden, and quality of life. Then, we review to which extent these factors have been considered in previously conducted resilience studies. Additionally, we discuss the significance of considering consumer disparities in developing frameworks, policies, and utility practices toward enhancing power system resilience. We also investigate the operational resources utilized in strategies implemented to improve system resilience and discuss their impacts on consumer perspectives. Finally, we provide suggestions for addressing consumers’ concerns in forthcoming resilience research. Differing from typical review papers, this review examines and analyses the importance of aligning power system resilience with consumer expectations. This alignment will ensure that electrical grids are not only technically robust but also equitable, accessible, and responsive to the needs of all consumers.